Clavicle fracture and triathlon performance: a case report - Gerdesmeyer, L.; Burgkart, R.; Saxena, A. (Journal of Medical Case Reports, 2024)
Background Collarbone fracture is a common injury, particularly among athletes involved in contact sports and participating in endurance activities. Conventional treatment requires surgery and postoperative immobilization, resulting in an average return-to-sport timeframe of approximately 13 weeks. This case challenges the established treatment protocols, aiming to expedite recovery and enable a quicker resumption of high-intensity athletic activities.